RHETORICAL MOVES VARIATIONS OF RESEARCH ARTICLE DISCUSSION SECTION PUBLISHED IN REPUTABLE JOURNALS - Ulya, Solihatul (Universitas Muhammadiyah Metro, 2022)
Publishing academic articles is no longer an option but an obligation among academics. Nevertheless, in reality, many students have difficulty writing research results in the form of articles. The current research aims to describe the arrangement of the discussion sections in research articles published in reputable journals and the difference between the research article discussion section in journals indexed with SINTA 1 and SINTA 2. A qualitative study content analysis is used in this research. The data in this study were analyzed using Yang & Allison's (2003) Models. Twenty discussions were taken as the primary data. At first, twenty research articles were selected from SINTA, ten discussions from S1, and the other ten articles were from S2. The articles selected here are those which were published in 2021. The research findings show that there are three moves that the authors always include, namely Move 2 (reporting results), Move 4 Step a (interpreting results), and Move 4 Step b (comparing results with literature). The findings also imply that the authors have used most of the moves and steps proposed by Yang & Allison's (2003) framework in compiling the discussion section. This research can benefit researchers, especially university students who want to submit their manuscripts to journals. By knowing what the editors want in writing the discussion section, mistakes can be minimized since the most revision is on this part.